Reducing Emergency Department Bounce-Back Through Nurse-Driven Discharge Education - Fountain, Madison (My University, 2024)
A bounce-back is an emergency department (ED) visit by a patient previously treated and discharged who has subsequently checked back in within 48 hours for treatment (Montoy et al., 2019). Bounce-backs constitute a significant healthcare problem, causing decreased health in our population and an increase in the total cost of healthcare (Curcio et al., 2020). The national bounce-back average is 4%, and healthcare systems implement few interventions to solve the issue despite support within the literature to justify that thorough nursing education at discharge lowers bounce-backs. Nurse-to-patient educational gaps in the ED discharge process have decreased emergency nurses' competence and confidence in discharge teaching. The primary objective of this DNP project was to determine if improved nursing education at the time of discharge would decrease bounce-backs. This DNP project found a correlation between bounce-backs and teach-back method implementation, which led to nurse-driven education during discharge. The IOWA method and the Institute for Health Improvement (IHI) recommendations were utilized to implement the teach-back method and incorporate an emergency nursing discharge tool. In this DNP project, many emergency nurses were unaware of bounce-backs, never used the teach-back method, and never received teach-back or discharge training. The project’s barriers included a small sample size, no standardized discharge tool or process, and response bias. The study's findings suggest that emergency nursing staff's increased attention to the discharge process positively impacts the rate at which bounce-backs are seen. Further education should focus on the vulnerable populations contributing to bounce-backs.
Keywords: Bounce-back, emergency nursing, emergency department, teach-back, discharge education